Outcome of Ileal Pouch-anal Anastomosis in Patients With Indeterminate Colitis: A Systematic Review and Meta-analysis. (8th January 2020) - Emile, Sameh Hany; Gilshtein, Hayim; Wexner, Steven D
Abstract: Background: Indeterminate colitis [IC] is type of inflammatory bowel disease that exhibits features of both ulcerative colitis [UC] and Crohn's disease [CD]. The present meta-analysis aimed to assess the outcomes of ileal pouch-anal anastomosis [IPAA] in patients with IC in comparison with patients with UC. Methods: A PRISMA-compliant systematic review of the outcome of IPAA in patients with IC was conducted. Electronic databases were searched, and full-text articles were reviewed to extract essential data. Main outcome measures were pouch failure and pouch-related complications. Results: A total of 17 studies were included in this meta-analysis. There were 1057 patients with IC and 6511 patients with UC. The weighted mean pouch failure rate in patients with IC was 7.5 (95% confidence interval [CI]: 4.8–10.2) and the weighted mean complication rate was 67 [95% CI: 53.5–80.5]. As compared with patients with UC, patients with IC had significantly higher odds of developing complications after IPAA (odds ratio [OR]: 2.6, p <0.001): pouch fistula [OR:4.98, p <0.001], pelvic sepsis [OR:3.98, p =0.002], pelvic or cuff abscess [OR: 4.5, p <0.001], perineal complications [OR: 5.13, p <0.001], and ultimate diagnosis of CD [OR: 2.57, p <0.001]. Patients with IC and UC had similar odds of pouch failure, pouchitis, anastomotic leak, stricture, and small bowel obstruction. Conclusions: Patients with IC had similar pouch failure rates, yet higher overall complication rates than patients with UC. Complications that tend to be higher after IPAA for patients with IC include pouch fistula, pelvic sepsis, abscess, perineal complications, and ultimate diagnosis of Crohn's disease.